Relevansi Konsep Persekutuan Perikhoresis Allah Tritunggal menurut Leonardo Boff bagi Kehidupan Sosial-Politik - Eugen Ervan Sardono; Vinsensius Rixnaldi Masut; Sebastianus Hagoldin (Jurnal Teologi (Journal of Theology), 2021)
This study is to explain the implication and relevance of a perichoresis communion of the Trinitarian God for a socio-political life. Relationship of the three persons of the triune God (Father, Son, and Holy Spirit) to one another reflects a profound equality as well as mutual respect though each has and exercises a different role to create a meaningful work together. These virtues of equality and mutual respect can serve as a model for our socio-political life in today’s world continuously marked by war, discrimination, injustice, poverty or totalitarianism. The research methodology used in this study is a library study of the concept of the fellowship of the Triune God, according to Leonardo Boff.. This study came to a conclusion that the respective model of Trinitarian perichoresis can really serve as a model of socio-political life and as encouragement to welcome and respect plurality as well as an improved democratic government